KONSELIG INDIVUDUAL MELALUI TEKNIK SELF MANAGEMENT DI SMP NEGERI 2 KADUNGORA - Suryadi Suryadi; Euis Eti Rohaeti; Wiwin Yuliani (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
AbstractThis research at SMP Negeri 2 Kadungora aims to determine how the implementation of individual counseling services through self-management techniques at SMP Negeri 2 Kadungora. This study uses a qualitative method where the researcher reveals and describes the data according to what is happening in the field. Data collection techniques using observation, interviews, and documentation. The subjects in this study were teachers of guidance and counseling. The sampling technique used was purposive sampling, which was purposive sampling in accordance with the required criteria or assessment. The results of this study indicate that based on the results of observations, interviews, and documentation studies conducted by researchers that the implementation of individual counseling services through the Self-management Technique at SMP Negeri 2 Kadungora is quite good, although there are still some shortcomings such as competent implementers, materials based on need assessment. , strategies according to the needs of students, carried out in a scheduled and incidental manner, the scope is in accordance with the personal field and adequate facilities and infrastructure provided by the schoolKeywords:Individual counseling, Self management techniques.